Global secondary indirect effects of topography, bathymetry, ice and sediments - TENZER, Robert; HAMAYUN; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2008)
When gravitational effects of density contrasts of various known structural crustal/geologic elements are to be removed from the topographically corrected gravity anomalies, this removal (stripping) consists not only of subtracting the direct effect of these density contrasts, but also of adding the secondary indirect effects of these density contrasts. In this study, we compile global maps of the secondary indirect effects of the topography, of the bathymetry, of ice, and of sediments.